. ; Ruptures in probability scale. Their manifestations in economics and forecasting - Alexander Harin (2010)
. . – – Proofs of theorems of existence of ruptures in finite numerical segments and in the probability scale are considered. The proofs are performed for the continuous case. Manifestations of these ruptures in economics and forecasting are touched upon.
Keywords: C; C1; D8; D81; C53; 330; probability theory; data dispersion; utility; economics; forecasting; Wahrscheinlichkeitsrechnung; Nutzentheorie; Prognoseverfahren